DESIGNING WITH EMOTIONAL AWARENESS - F. Bianconi; M. Filippucci; G. Magrini; M. Seccaroni (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2021)
The Italian school building heritage built between the seventies and eighties is every year increasingly abandoned and it remains in a state of neglect. It is increasingly necessary a recovery and enhancement methodology that preserves the memory of the place and at the same time, it makes it capable of adapting to the new needs of the city. The proposed research project originates from the study of the interactions between man and the environment applied to an architectural context with the identification of emotions. This methodology applied to citizenship, aims to make the population participate in the improvement from the point of view of well-being. This process was possible thanks to the combined use of immersive reality (VR) and the use of the GEW model, the data of which are the foundation and verification of the choices of architectural design, analyzed through the impacts on humans.